Characterisation of NeuLAND scintillator bars and timing in the S406 experiment - Babic, Vedad (My University, 2014)
At the R3B (Reactions with Relativistic Radioactive Beams) experiment at FAIR (Facility for Antiproton and Ion Research) studies regarding nuclear structure and dynamics will be performed using exotic nuclei far from stability. One of the main components in the R3B setup is the neutron detector NeuLAND (New Large Area Neutron Detector). A method for the characterisation of plastic scintillator bars for use in NeuLAND involving cosmic muon and LED measurements has been evaluated. The method involves an LED (Light Emitting Diode) as a photon source and a PMT (Photo Multiplier Tube)which are placed on opposite sides of the bar. The attenuation of light intensity from the LED is measured with the PMT simultaneously as cosmic muons impinge on the bar. In order to characterise the bar as having a sufficiently good response, both the cosmic muon and LED response need to be above 90% of the response of a reference bar. Due to the need of accurate time measurements, two approaches to determine if the walk-effect is present in a time-of-flight wall were considered i.e. if time measurements depend on the energy deposited in the scintillator bar. The first one by analysing data in experiment S406 and extracting the time-of-flights from the start detector, POS to the detector of interest. From this number, a calculated time-of-flight was subtracted. It is seen that there exists an energy dependence on the time measurements and a walk-effect is observed. The observed walk is in the order of several ns. The second approach was to try to determine the walk with the Land02 walk programme which yielded walk curves as well. The walk in this case was in the order of 1-2 ns which agrees with the previous results. An attempt to correct for the walk by approximating the walk function with a linear polynomial did not improve the time measurements.
Keywords: Grundläggande vetenskaper; Fysik; Subatomär fysik; Kärnfysik; Tungjonsfysik; Basic Sciences; Physical Sciences; Subatomic Physics; Nuclear physics; Heavy ion physics